The role of financial development in the oil-growth nexus - Moradbeigi, Maryam; Siong, Hook Law (Elsevier, 2017)
It is expected that possessing the natural resources could faster increases the pace of growth in natural resource endowed countries. However, history has shown that this is not the case for some resource rich countries. In the current study, hence, we assess whether more developed financial markets can channel the revenues from oil into more productive activities and thus offset the negative effects of oil abundance on growth. To this end, we adopt the common correlated effect mean group estimator to account for the high degree of heterogeneity (because of substantial cross-sectional dependence in our data) for a core sample of 63 oil-producing countries from 1980 through 2010. The empirical results show that oil abundance affects the growth rate in output based on the degree of development in financial markets. In other words, better financial development dampens the negative impact of oil abundance on economic growth.